-10(p+3)=-10

Simple and best practice solution for -10(p+3)=-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10(p+3)=-10 equation:


Simplifying
-10(p + 3) = -10

Reorder the terms:
-10(3 + p) = -10
(3 * -10 + p * -10) = -10
(-30 + -10p) = -10

Solving
-30 + -10p = -10

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '30' to each side of the equation.
-30 + 30 + -10p = -10 + 30

Combine like terms: -30 + 30 = 0
0 + -10p = -10 + 30
-10p = -10 + 30

Combine like terms: -10 + 30 = 20
-10p = 20

Divide each side by '-10'.
p = -2

Simplifying
p = -2

See similar equations:

| 12+2abc= | | 7(14/2) | | 4756927845983746abc+65xyz= | | u=24 | | 18=b+10 | | 4(1.5c+6)-2c=24 | | f=2h | | X^3-2x^3-x+2=0 | | 3(x-6)+9=-9 | | 29=5x-2(10-x) | | (2/3)(k-8)=52 | | 9.7y+2.16=11.42 | | y-11=(5/11)(x-10) | | 0.25(16-4x)=7-(1.25x+5) | | x-5y=17fory | | 4g+17=81 | | Xsquared+8x+15=0 | | 73774t+132=11 | | 4(2-3x)-(6x-4)=2(5-5x) | | h=32+48t-16t^2 | | 8n+19=4n+135 | | 2(3.14r)=20 | | 2x+8=25-9x | | 3*(X+2)=15 | | -6.1y=198.25 | | 12c-5c= | | w-16=28 | | 2/3x13 | | 5x^2+21x-4=0 | | -[-[-(6x+5)]]=-(x+5) | | 2(3p-t)-(-4p+t)= | | 24+p=54 |

Equations solver categories